Providing culturally informed mental health services to Aboriginal youth: The YouthLink model in Western Australia. Issue 5 (24th March 2018) - Sabbioni, Daniela; Feehan, Steven; Nicholls, Craig; Soong, Wei; Rigoli, Daniela; Follett, Denise; Carastathis, Geoff; Gomes, Alison; Griffiths, Jennifer; Curtis, Kerry; Smith, Warwick; Waters, Flavie
Abstract : Aim: Aboriginal young people are more likely to experience mental health issues and to access mental health services than other young Australians, yet there are few culturally informed mental health programs and services available. This study describes and documents the effectiveness of the culturally sensitive model within YouthLink, a state‐wide mental health service program in Western Australia for young people aged 13 to 24 years of age. Methods: A mixed‐method design including a descriptive approach reporting on the YouthLink framework and an empirical research design where 40 Aboriginal clients completed client feedback monitoring measures between 2014 and 2016. Results: The YouthLink culturally informed conceptual framework adheres to best practice principles relevant to work with Indigenous people, family and communities. Aboriginal young people indicated improvement across the treatment period as shown by within‐group differences between the first and last session scores on feedback measures. Therapeutic alliance (together with lower baseline acuity and female gender) also contributed significantly to positive treatment outcomes. Conclusions: Through a strong role of Aboriginal practitioners, relationships with Aboriginal communities, and greater service flexibility that embraces cultural meaning and knowledge, YouthLink has sought to enhance its response to the needs of Aboriginal youth.